Telling the truth : how to make verbatim theatre - Belfield, Robin (Making theatre (London, England), 2018)
A practical guide to creating and producing verbatim theatre, by an experienced theatre-maker and practitioner. Verbatim theatre is fashioned from words actually spoken by real people in real situations, and reproduced by actors in performance. An increasingly influential form of theatre, it has a unique ability to present stories from unfamiliar sources and bring unheard voices to the stage. Verbatim theatre is perhaps the most objective way of dramatising real life; its authenticity helps audiences to understand the world we live in, whether through testimony, eye-witness accounts or autobiography. Telling the Truth offers a step-by-step breakdown of the entire process of making your own verbatim-theatre production, covering everything you need to consider, including: - Choosing your subject - Preparing and conducting your interviews - Refining your research into a single narrative strand - Editing your material sensitively and ethically - Providing your actors with exercises, techniques and advice to allow them to perform as 'real' people - Designing and staging your work for fully realised, physical performance In Telling the Truth, Robin Belfield draws on his own experiences of creating verbatim-theatre work, and interviews other major directors, writers and actors including Alecky Blythe, Patrick Sandford, Hilary Maclean and ACH Smith, providing tips and advice to help you make the most of every part of the verbatim-theatre process. An essential how-to guide for theatre-makers, artists, students and teachers who want to create their own verbatim-theatre production, Telling the Truth is also a fascinating read for those interested in the processes and inspirations that created the productions they love.